1998
DOI: 10.1007/s005340050075
|View full text |Cite
|
Sign up to set email alerts
|

Serous cystadenocarcinoma of the pancreas with liver metastases

Abstract: Serous cystadenocarcinoma of the pancreas is a rare entity. We report a primary tumor of the pancreas in a 56-year-old woman that was histologically indistinguishable from microcystic adenoma, but which behaved in a malignant fashion. Metastatic lesions were found in the liver at the time of the initial operation. Nine years after the initial operation, new metastatic liver nodules were found, and the histologic characteristics of these lesions were quite similar to those of the pancreatic neoplasm. This is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 8 publications
2
36
1
2
Order By: Relevance
“…2,4 Furthermore, although serous cystic neoplasms are almost entirely benign, some malignant cases that involve the adjacent organs and/or metastasize to the liver have been reported. [5][6][7] Patients who have symptoms associated with serous cystic neoplasms usually require surgical treatment. 1,2 Mucinous cystic neoplasms develop almost exclusively in middle-aged and elderly women, and are associated with a significant risk of malignant change from adenoma to carcinoma.…”
mentioning
confidence: 99%
“…2,4 Furthermore, although serous cystic neoplasms are almost entirely benign, some malignant cases that involve the adjacent organs and/or metastasize to the liver have been reported. [5][6][7] Patients who have symptoms associated with serous cystic neoplasms usually require surgical treatment. 1,2 Mucinous cystic neoplasms develop almost exclusively in middle-aged and elderly women, and are associated with a significant risk of malignant change from adenoma to carcinoma.…”
mentioning
confidence: 99%
“…A handful of malignant serous cystic neoplasms, serous cystadenocarcinomas, have been reported. 129,[153][154][155][156][157][158][159][160][161] Most of these were microscopically identical to serous cystadenomas, and no morphologic findings, other than behavior, have been found to distinguish these malignant variants from their benign counterparts. In fact, in some, the diagnosis of malignancy was established only after metastases to the liver were detected.…”
Section: Serous Cystadenocarcinomasmentioning
confidence: 99%
“…In the interior they form a honeycomb appearance, or a sponge-like structure with numerous small closely packed cysts arranged around a central stellate calcified scar (Buck and Hayes, 1990). There are very few cases of microcystic adenocarcinomas reported (Abe et al, 1998;Eriguchi et al, 1998;Wu et al, 1999). Histologically both microcystic adenomas and microcystic adenocarcinomas are identical and the presence of metastasis in liver or lymph nodes is the only way to differentiate them.…”
Section: Serous Cystic Neoplasms (Scns)mentioning
confidence: 99%
“…The incidence of serous cystadenocarcinoma is very low (Abe et al, 1998;Eriguchi et al, 1998;Wu et al, 1999). The multicenter study of SCNs in Japan showed that out of 172 patients with SCNs only 2 had liver metastasis (Kimura et al, 2012).…”
Section: Surgerymentioning
confidence: 99%